2020
DOI: 10.5114/aoms.2020.95336
|View full text |Cite
|
Sign up to set email alerts
|

Particulate matter pollution and the COVID-19 outbreak: results from Italian regions and provinces

Abstract: Particulate matter exposure has been associated with the appearance and severity of several diseases, including viral infections. The aim of this study was to investigate whether coronavirus disease 2019 (COVID-19) cases and deaths across Italian regions and provinces in March 2020 were linked to past exposure to fine and coarse particulate matter (namely, PM 2.5 and PM 10 , respectively). Material and methods: Geographical distributions of COVID-19 cases and deaths (105,792 and 12,428, respectively, up to 31 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
67
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 29 publications
13
67
0
Order By: Relevance
“…The fact that both incidence and mortality were positively correlated with population density is in line with our knowledge about the spread of the virus and confirms that measures to reduce viral transmission, focusing on social distancing in particular, are reasonable [12][13][14][15][16]. The positive correlation between COVID-19 incidence and the proportion of the population aged above 65 suggests that older adults are more likely to get infected, which has been observed in other countries as well [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 83%
“…The fact that both incidence and mortality were positively correlated with population density is in line with our knowledge about the spread of the virus and confirms that measures to reduce viral transmission, focusing on social distancing in particular, are reasonable [12][13][14][15][16]. The positive correlation between COVID-19 incidence and the proportion of the population aged above 65 suggests that older adults are more likely to get infected, which has been observed in other countries as well [17][18][19][20][21][22].…”
Section: Discussionsupporting
confidence: 83%
“…In a study in China 7 , a positive association has been observed between COVID cases and major criteria pollutants (PM 2.5 , PM 10 , NO 2 ,O 3 and CO) except SO 2 . A similar positive association between COVID cases and PM 2.5 exposure was obtained from Italy 8 . While these studies examined the association between COVID cases and short-term exposure to air pollution, chronic exposure to air pollution is also being considered as a risk of COVID outbreak 9 .…”
Section: Introductionsupporting
confidence: 80%
“…Previous literature has established associations between exposure to air pollution and spread of measles 14,15 and spread of respiratory diseases 16,17 . Speci cally, in case of COVID, studies from China 7 and Italy 8,9 have shown air pollution to be an important factor in disease transmission and mortality. Our study provides evidence from India which is currently witnessing a rapid rise in COVID cases and has a signi cant proportion of its population residing in areas with poorest air quality in the world.…”
Section: Resultsmentioning
confidence: 99%
“…By comparing the number of cloudy days of throat swab nucleic acid in patients treated with lopinavir/ritonavir and Abidol, it was found lopinavir/ritonavir and Abidol may not be effective in treating COVID-19; however, the number of cases in this study was small, and further research using large sample data should be conducted to determine their effectiveness. In terms of susceptibility to COVID-19, Bianconi et al found that particulate matter pollution significantly increased the probability of infection with COVID-19 [32]. This may also serve as a warning about the over-modification of nature by human beings.…”
Section: Discussionmentioning
confidence: 99%